How to reactivate the Alumni-UNICAMP Platform from the Alumni-UC Network - Godoy, Andréa Cristina Tavares Franco de (ICAReAlumni Conference Proceedings, 2023)
This article shares the experience of international mobility promoted by the Executive Board of International Relations at the State University of Campinas in partnership with Banco Santander. I will report my experience during international mobility at the University of Coimbra, more specifically with the International Relations Division sector. The main objective of the visit was to seek experiences to identify actions that culminated in the high adherence of the Alumni at the University of Coimbra. Therefore, I got to know the platform and the work carried out by the Alumni team of the University of Coimbra in depth. I intend to incorporate the knowledge acquired in order to publicize the platform and attract new Alumni from the Institute of Biology at Unicamp.